Pelatihan pemanfaatan aplikasi Kahoot! sebagai Assessment Edutainment bagi guru Sekolah Dasar - Sekar Dwi Ardianti; Himmatul Ulya (Universitas Hamzanwadi, 2022)
The Covid-19 pandemic has had an adjustment impact on all sectors, including the education sector in Indonesia. To overcome this, the Government of Indonesia implements online and offline learning. However, the teacher's unpreparedness in dealing with changes in the learning system is one of the obstacles in online education, especially the use of digital learning media. So it is necessary to assist in developing good learning media and assessments. This community service activity aims to teach teachers at SD 2 Peganjaran about using Kahoot! as an Assessment Edutainment system. The method used in this service is to provide interactive training and mentoring. Furthermore, two-way interaction in the training process allows teachers at SD 2 Peganjaran as training participants to contribute ideas, opinions, thoughts, and experiences. The mentoring participants consisted of 12 teachers and the school principal. Implementation of assistance in the use of Kahoot! Software as an edutainment assessment system for teachers at SD 2 Peganjaran was designed in several stages, including planning, implementation, follow-up, and evaluation. The result of this community service activity is that teachers at SD 2 Peganjaran can use Kahoot! as an edutainment assessment system. The results obtained from the community service activities were that teachers at SD 2 Peganjaran were 84.6% able to make instruments using Kahoot! as an Edutainment Assessment system for online learning. Assistance in using applications for online learning assessments provides teachers with knowledge and skills to utilize and compile assessments using Kahoot! as an Edutainment Assessment system for online learning.